Powered by www.myengg.

com

DIFFERENTIAL EQUATIONS
PREVIOUS EAMCET BITS 1. The solution of the differential equation

dy = sin ( x + y ) tan ( x + y ) − 1 is dx 2) x + cos ec ( x + y ) = c 4) x + sec ( x + y ) = c

[EAMCET 2009]

1) cos ec ( x + y ) + tan ( x + y ) = x + c 3) x + tan ( x + y ) = c Ans: 2 Sol: Let x + y = v
1+ dy dv = dx dx dv − 1 = sin v tan v − 1 dx

we have,

dv = sin v tan v dx
dv sin 2 v cos v = ⇒ ∫ 2 dt = ∫ dx 2 dx cos v sin v
− 1 = x+c sin v

∴ cosec(x + y) + x = c
2. The differential equation of the family y = ae x + bxe x + cx 2 e x of curves, where a, b, c arbitrary [EAMCET 2009] constants, is

1) y′′′ + 3y′′ + 3y′ = 0 3) y′′′ − 3y′′ − 3y′ + y = 0 Ans: 4 Sol: y = ae x + bxe x + cx 2 e x

2) y′′ + 3y′′ − 3y′ = 0 4) y′′′ − 3y′′ + 3y′ − y = 0

y = ( a + bx + cx 2 ) e x d.b.s.w.r.t ‘x’
y′ = ( a + bx + cx 2 ) e x + e x ( b + 2cx ) y′ = y + e x ( b + 2cx ) y′′ = y′ + e x ( 2cx ) + ( b + 2cx ) e x y′′ = y′ + y′ − y + 2cxe x

84

Powered by www.myengg.com

Powered by www.myengg.com

Differential Equations

y′′ = 2y′ − y + 2cxe x y′′′ = 2y′′ − y′ + 2ce x y′′′ = 2y′′ − y′ + [ y′′ − 2y′ + y ] ∴ y′′′ − 3y′′ + 3y′ − y = 0 3. The solution of the differential equation
1) ( x − 2y ) + 2x = c
2

dy x − 2y + 1 = is dx 2x − 4y 2) ( x − 2y ) + x = c
2

[EAMCET 2008]

⎛ cx ⎞ 3) x − y = log ⎜ ⎟ ⎝ y ⎠ Ans: 1 Sol: Put x − 2y = z . Then 1 − 2

4) ( x − 2y ) + x 2 = c

dy dz dy dz dy 1 ⎛ dz ⎞ ⇒ = ⎜1 − ⎟ = ⇒2 = 1− dx 2 ⎝ dx ⎠ dx dx dx dx

dy x − 2y + 1 1 ⎛ dz ⎞ z + 1 dz 1 = ⇒ ⎜1 − ⎟ = ⇒ 1− = 1+ dx z dx 2x − 4y 2 ⎝ dx ⎠ 2z
⇒ 4. dz −1 z2 2 = ⇒ zdz = −dx ⇒ = − x + c / 2 ⇒ z 2 = −2x + c ⇒ ( x − 2y ) + 2x = c dx z 2 dy − y tan x = e x sec x is dx 3) y = e x sin x + c
[EAMCET 2008]

The solution of the differential equation 1) ye x cos x + c Ans: 2 2) y cos x = e x + c

4) y sin x = e x + c

Pdx − tan xdx = cos x Sol: I.F = e ∫ = e ∫

The solution is y cos x = ∫ e x sec x cos xdx = ∫ e x dx = e x + c ⇒ y cos x = e x + c 5. The solution of the differential equation xy 2dy − ( x 3 + y3 ) dx = 0 is 1) y3 = 3x 3 + c Ans: 2 Sol: Put y = vx. Then dy dν =ν+ dx dx dy x 3 + y3 dv x 3 + x 3 v3 dv 1 = ⇒ν+x = ⇒ v+x = +v 2 3 2 dx dx dx v 2 xy xν 2) y3 = 3x 3 log ( cx )

[EAMCET 2008]

3) y3 = 3x 3 + log ( cx ) 4) y3 + 3x 3 = log ( cx )

xy 2 dy − ( x 3 + y3 ) dx = 0 ⇒ ⇒x

dν 1 dx ν 3 = 2 ⇒ ν 2 dν ⇒ = = log x + log c dx ν x 3

85

Powered by www.myengg.com

Powered by www.myengg.com

Differential Equations ⇒ ν 3 = 3log ( cx ) ⇒ ∴ y3 = 3x 3 log ( cx ) 6. The differential equation obtained by eliminating the arbitrary constants a and b from xy = ae x + be − x is 1) x 3) x d2 y dy + 2 − xy = 0 2 dx dx d2 y dy +2 −y=0 2 dx dx 2) 4) d2 y dy + 2y − xy = 0 2 dx dx d 2 y dy + − xy = 0 dx 2 dx y3 = 3log ( cx ) x3

[EAMCET 2007]

Ans: 1 Sol: xy = ae x + be − x ⇒ xy1 + y = ae x − be − x xy 2 + y1 + y1 = ae x + be− x
∴ xy 2 + 2y1 − xy = 0 7. The solutions of ( x + y + 1) dy = 1 is dx 3) x = − ( y + 2 ) + ce y

[EAMCET 2007]
4) x = ( y + 2 ) + ce y
2

1) y = ( x + 2 ) + ce x 2) y = − ( x + 2 ) + ce x Ans: 3 Sol: Put x + y + 1 = z ⇒ dy dz = −1 dx dx

( x + y + 1)

dy ⎛ dz ⎞ = 1 ⇒ z ⎜ − 1⎟ = 1 dx ⎝ dx ⎠

dz 1 z = 1+ ⇒ ∫ dz = ∫ dx dx z z +1

⇒ z − log ( z + 1) = x + c
x + y + 1 = x + log ( x + y + 2 ) + c

y = log ( x + y + 2 ) + log c
⇒ x + y + 2 = ce y

8.

The solution of 1) e y / x = kx Ans: 2

dy y2 = is dx xy − x 2 2) e y / x = ky 3) e − y / x = kx

[EAMCET 2007]
4) e − y / x = ky

86

Powered by www.myengg.com

Powered by www.myengg.com

Differential Equations Sol: Put y = vx dy y2 dV V2 = ⇒V+x = dx xy − x 2 dx V − 1

⇒∫

V −1 1 dV = ∫ dx V x

⇒ V − log V = log x + log c
⇒ V = log ( cVx ) ∴ cy = e y / x

9.

The solution of 1) e
−( x + y )

dy + 1 = e x + y is dx
−( x + y )

[EAMCET 2007]
3) e x + y + x + c = 0 4) e x + y − x + c = 0

+ x + c = 0 2) e

−x+c = 0

Ans: 1 Sol: Put x + y = z ⇒ 1 + dy dz = dx dx

dz = e z ⇒ ∫ e − z dz = ∫ dx dx
−e − z = x + c ⇒ e
−( x + y )

+x+c=0

10.

The solution of ( x 2 + y 2 ) dx = 2xy dy is 1) c ( x 2 − y 2 ) = x Ans: 1 2) c ( x 2 + y 2 ) = x 3) c ( x 2 − y 2 ) = y

[EAMCET 2006]
4) c ( x 2 + y 2 ) = y

Sol: Homogeneous differential equation y 1 + V2 ′x = Put = V ⇒ V + V x 2V
⇒∫

2V dx ⇒ − log 1 − v 2 = log x + log c dV = ∫ 2 1− V x

Solving c ( x 2 − y 2 ) = x 11. The solution of (1 + x 2 ) 1) 3x (1 + x 2 ) = 4x 3 + c 3) 3x (1 − x 2 ) = 4x 3 + c Ans: 2 Sol: dy ⎛ 2x ⎞ 4x 2 +⎜ y= ⎟ dx ⎝ 1 + x 2 ⎠ 1+ x2 87

dy + 2xy − 4x 2 = 0 is dx
2) 3y (1 + x 2 ) = 4x 3 + c 4) 3y (1 − x 2 ) = 4x 3 + c

[EAMCET 2006]

Powered by www.myengg.com

Powered by www.myengg.com

Differential Equations Linear differential equation I.F = e ∫
pdx

dy + P(x) y = Q(x) dx

=e

∫ 1+ x 2 dx

2x

= 1+ x2

y. (1 + x 2 ) = ∫ y. (1 + x 2 ) =

4x 2 1 + x 2 ) dx 2 ( 1+ x

4x 3 +c 3

3y (1 + x 2 ) = 4x 3 + c
12. The solution of 1) dx x + = x 2 is dy y 3) 1 = cx + x log y x 4)

[EAMCET 2006]
1 = cx − y log x y

1 1 = cx − x log x 2) = cy − y log y x y

Ans: 2 Sol: -----13. dx + dy = ( x + y )( dx − dy ) ⇒ log ( x + y ) = 1) x + y + c Ans: 3 Sol: 2) x + 2y + c 3) x − y + c

[EAMCET 2005]
4) 2x + y + c

dx + dy = dx − dy x+y

d ( x + y) ∫ ( x + y ) = ∫ dx −∫ dy
log ( x + y ) = x − y + C

14.

x 2 y − x3
1) sinx Ans: 3

dy = y 4 cos x ⇒ x 3 y −3 = dx
2) 2sin x + c dy = y 4 cos x dx 3) 3sin x + c

[EAMCET 2005]

4) 3co s x + c

Sol: x 2 y − x 3

x 2 ydx − x 3dy = cos x y 4 dx
= x2 x3 dx − 4 dx = cos xdx y3 y

⎛ x3 ⎞ ⇒ ∫ d ⎜ 3 ⎟ = 3sin x + C ⎝y ⎠
88

Powered by www.myengg.com

Powered by www.myengg.com

Differential Equations ⎛ 3x 3 3x 3 ⎞ ∫ ⎜ y3 dx − y4 dy ⎟ = ∫ 3cos xdx ⎝ ⎠ ⇒ 15. x3 = 3sin x + C y3

Observer the following statements :

[EAMCET 2005]

I. dy + 2xydx = 2e − x ⇒ ye x = 2x + C
2 2

II. ye 2 2x = c ⇒ dx = 2e − x − 2xy dy
2

Which of the following is a correct statements 1) Both I and II are true 3) I is true , II is false Ans: 3 Sol:
2 dy + 2x.y = 2e − x dx

2) Neither I nor II is true 4) I is false, II is true

which is linear differential equation

I.F = e ∫
2

2xdx

= ex
2

2

y.e x = ∫ 2.e− x e x dx = 2x + C True. ∴ I is true, II is false
2

16.

dy y + x tan y / x y = ⇒ sin = dx x x
1) cx2 Ans: 2 2) cx 3) cx3 4) cx4

[EAMCET 2005]

Sol: Put

y dy dv =V⇒ = V+x x dx dx dv = V + TanV dx
dv x

V + x.
dv

∫ tan V = ∫

log sin V = log Cx ⎛y⎞ sin ⎜ ⎟ = Cx ⎝x⎠
17. Integrating factor of ( x + 2y3 ) 1) e
⎛1⎞ ⎜ ⎟ ⎝ y⎠

dy = y 2 is dx 3) y 4) −1 y

[EAMCET 2004]

2) e

⎛1⎞ −⎜ ⎟ ⎝ y⎠

Ans: 1
89

Powered by www.myengg.com

Powered by www.myengg.com

Differential Equations Sol: dx x = + 2y dy y 2 ⎛ 1 ⎞ dx + x ⎜ − 2 ⎟ = 2y dy ⎝ y ⎠
I.F = e 18. ∫ − y2 dy
1

=e

1 y

y = Ae x + Be2x + Ce3x satisfies the differential equation 1) y ′′′ − 6y′′ + 11y ′ − 6y = 0 3) y ′′′ − 6y′′ − 11y ′ − 6y = 0 Ans: 1 2) y ′′′ + 6y′′ + 11y′ − 6y = 0 4) y ′′′ − 6y′′ − 11y ′ + 6y = 0

[EAMCET 2004]

Sol: y′′′ − (1 + 2 + 3) y′′ + (1.2 + 2.3 + 3.1) y′ − 1.2.3y = 0 19. Observe the following statements : A : Integrating factor of R : Integrating factor of

[EAMCET 2004]

dy + y = x 2 is e x dx
P ( x ) dx dy + P ( x ) y = Q ( x ) is e ∫ dx

Then the true statement among the following is 1) A is true, R false 3) A is true, R is true, R ⇒ A Ans: 3 Sol: I.Fof 20.
1dx dy + y = x 2 is e ∫ = e x dx

2) A is false, R is true 4) A is false, R is false

The differential equation of the family of parabola with focus at the origin and the X-axis as axis [EAMCET 2003] is

⎛ dy ⎞ ⎛ dy ⎞ 1) y ⎜ ⎟ + 4x ⎜ ⎟ = 4y ⎝ dx ⎠ ⎝ dx ⎠ dy ⎛ dy ⎞ 3) y ⎜ ⎟ + y = 2xy dx ⎝ dx ⎠ Ans: 2 Sol: Focus = (0, 0); directrix is x+ a = 0 Equation of the parabola is y2 = a(2x + a)
2

2

dy ⎛ dy ⎞ 2) − y ⎜ ⎟ = 2x −y dx ⎝ dx ⎠ ⎛ dy ⎞ ⎛ dy ⎞ 4) y ⎜ ⎟ + 2xy ⎜ ⎟ + y = 0 ⎝ dx ⎠ ⎝ dx ⎠
2

2

90

Powered by www.myengg.com

Powered by www.myengg.com

Differential Equations
2y dy = 2a ⇒ a = yy1 dx 2 y 2 = 2xyy1 + y 2 y1

2 ⇒ y 2 = y ⎡ 2xy1 + yy1 ⎤ ⎣ ⎦ 2 ⇒ y = 2xy1 + yy1 2 ⇒ − yy1 = 2xy1 − y

⎛ dy ⎞ ⎛ dy ⎞ ⇒ − y ⎜ ⎟ = 2x ⎜ ⎟ − y ⎝ dx ⎠ ⎝ dx ⎠ 21. Solution of dy x log x 2 + x is = dx sin y + y cos y
2) y sin y = x 2 + c 4) y sin y = x log x + c

2

[EAMCET 2003]

1) y sin y = x 2 log x + c
3) y sin y = x 2 + log x + c Ans: 1 Sol: dy x log x 2 + x = dx sin y + y cos y

⇒ sin ydy + y cos ydy = x log x 2 dx + xdx
Integrating on both sides y sin y = x 2 log x 2 + C 22. The general solution of y 2 dx + ( x 2 − xy + y 2 ) dy = 0 is

[EAMCET 2003]

⎛x⎞ 1) tan −1 ⎜ ⎟ + log y + c = 0 ⎝y⎠
3) log y + x 2 + y 2 + log y + c = 0 Ans: 1 Sol: dy − y2 = 2 dx x − xy + y 2 Put y = vx

⎛x⎞ 2) 2 tan −1 ⎜ ⎟ + log y + c = 0 ⎝y⎠ ⎛x⎞ 4) 2sinh −1 ⎜ ⎟ + log y + c = 0 ⎝y⎠

(

)

91

Powered by www.myengg.com

Powered by www.myengg.com

Differential Equations

v+x

dv −v2 x 2 −v2 = 2 = dx x − vx 2 + v 2 x 2 1 − v + v 2 dx 1 − v + v2 dv =− x v (1 + v 2 )

log xv = tan −1 v + c ⎛y⎞ log y = tan −1 ⎜ ⎟ + c ⎝x⎠ ⎛x⎞ ⇒ log y + tan −1 ⎜ ⎟ + c = 0 ⎝y⎠ 23. Order of the differential equation of the family of all concentric circles centered at (h, k) is [EAMCET 2002] 1) 1 Ans: 1 Sol: 2) 2
2

3) 3

4) 4

(x − h)

+ ( y − k ) = r2
2

Centre (h, k) is fixed Radius = r is a variable Hence order is 1 24. The solution of 1) y = 3 + ce x / 3 Ans: 2 Sol: dy y + =1⇒ dx 3 Integrating factor : I.F = e

dy y + = 1 is dx 3
2) y = 3 + ce − x / 3 3) 3y = c + e x / 3

[EAMCET 2002]

4) 3y = c + c− x / 3

∫ 3 dx

1

= ex / 3

Solution ye x / 3 = ∫ e x / 3 dx ye x / 3 = 3e x / 3 + C y = 3 + Ce− x / 3 25. y + x2 = dy has the solution dx 2) y + x + 2x 2 + 2 = ce x 4) y 2 + x + x 2 + 2 = ce2x
[EAMCET 2002]

1) y + x 2 + 2x + 2 = ce x 3) y + x + x 2 + 2 = ce 2x Ans: 1 Sol: y + x 2 = dy dx

92

Powered by www.myengg.com

Powered by www.myengg.com

Differential Equations
dy − y = x2 dx −1dx = e− x I.F = e ∫ Solution ye− x = ∫ x 2 e − x dx ye− x = −e− x ( x 2 + 2x + 2 ) + C y + x 2 + 2x + 2 = Ce x 26. dy ⎛ y ⎞ The solution of =⎜ ⎟ dx ⎝ x ⎠ 1) x 2 / 3 + y 2 / 3 = c Ans: 2 Sol: dy y1/ 3 = 1/ 3 ⇒ y −1/ 3dy = x −1/ 3dx dx x
1/ 3

is 3) x1/ 3 + y1/ 3 = c

[EAMCET 2002]
4) y1/ 3 − x1/ 3 = c

2) y 2 / 3 − x 2 / 3 = c

∫y

−1/ 3

dy = ∫ x −1/ 3 dx

3 2/3 ⎡ y − x 2 / 3 ⎤ = C1 ⎦ 2⎣ ⇒ y2 / 3 − x 2 / 3 = C 27. The solution of xdx + ydy = x 2 ydy − xy 2 dx is 1) x 2 − 1 = c (1 + y 2 ) 3) x 3 − 1 = c (1 + y3 ) Ans: 1 Sol: xdx + ydy = x 2 ydy − xy 2 dx 2) x 2 + 1 = c (1 − y 2 ) 4) x 3 + 1 = c (1 − y3 )

[EAMCET 2001]

x (1 + y 2 ) dx = − y (1 − x 2 ) dy
−x y dx = dy 2 1− x 1 + y2 x y ∫ x 2 − 1 dx = ∫ 1 + y2 dy ⇒ log ( x 2 − 1) = log (1 + y 2 ) + log c ∴x 2 − 1 = c (1 + y 2 ) 28. The solution of x 2 + y 2

dy = 4 is dx
3) x 3 + y3 = 3x + c

[EAMCET 2001]
4) x 3 + y3 = 12x + c

1) x 2 + y 2 = 12x + c 2) x 2 + y 2 = 3x + c Ans: 4

93

Powered by www.myengg.com

Powered by www.myengg.com

Differential Equations Sol: x 2 + y 2
2

dy =4 dx
2

( 4 − x ) dx = y dy ∫ ( 4 − x ) dx = ∫ y dy
2 2

x 3 + y3 = 12x + c 29. The solution of 1) 2y = e 2x + c Ans: 3 Sol:

dy + y = e x is dx
2) 2ye x + e x + c 3) 2ye x = e 2x + c

[EAMCET 2001]
4) 2ye 2x = 2e x + c

dy + y = ex dx P = 1; Q = x
I.F is e ∫
pdx

= ex

y.e x = ∫ e x .e x + c ⇒ 2ye x = e 2x + c 30. If c is a parameter, then the differential equation whose solution is y = c 2 + ⎛ dy ⎞ ⎛ dy ⎞ 1) y = x ⎜ ⎟ − x ⎜ ⎟ ⎝ dx ⎠ ⎝ dx ⎠
4 2 4 2

c [EAMCET 2000] x

⎛ dy ⎞ ⎛ dy ⎞ 2) y = x ⎜ ⎟ + x ⎜ ⎟ ⎝ dx ⎠ ⎝ dx ⎠
4

2

⎛ dy ⎞ ⎛ dy ⎞ 3) y = x ⎜ ⎟ − x ⎜ ⎟ ⎝ dx ⎠ ⎝ dx ⎠ Ans: 3 Sol: y = c 2 +

⎛ d2 y ⎞ ⎛ dy ⎞ 4) y = x 4 ⎜ 2 ⎟ − x ⎜ ⎟ ⎝ dx ⎠ ⎝ dx ⎠

C dy −C ⇒ = x dx x 2
dy dx
2

⇒ C = −x 2

dy ⎞ 1 ⎛ 2 dy ⎞ ⎛ y = ⎜ −x 2 ⎟ + ⎜ −x ⎟ dx ⎠ x⎝ dx ⎠ ⎝ ⎛ dy ⎞ ⎛ dy ⎞ ⇒∴ y = x ⎜ ⎟ − x ⎜ ⎟ ⎝ dx ⎠ ⎝ dx ⎠
4 2

31.

The equation of curve passing through the origin and satisfying the differential equation dy 2 [EAMCET 2000] = ( x − y ) is dx 1) e 2x (1 − x + y ) = (1 + x − y ) 3) e 2x (1 − x + y ) = − (1 + x + y ) 2) e 2x (1 + x − y ) = (1 − x + y ) 4) e 2x (1 + x + y ) = (1 − x + y )

94

Powered by www.myengg.com

Powered by www.myengg.com

Differential Equations Ans: 1 Sol:

dy 2 = ( x − y ) Let x − y = t dx
dy dt = 1− dx dx dt dt 1− = t 2 ⇒ dx = dx 1 − t2 dt ⇒ ∫ dx = ∫ (1 − t 2 ) ⇒ 1 ⎛1+ t ⎞ ⎛1+ t ⎞ log e ⎜ ⎟ ⇒ 2x = log ⎜ ⎟ 2 ⎝1− t ⎠ ⎝1− t ⎠ 1+ t ⇒ e 2x = 1− t 2x ∴ e (1 − x + y ) = (1 + x − y ) x=

95

Powered by www.myengg.com